Pengaruh Pemberian Video Be-Fast Terhadap Pengetahuan Keluarga Pasien Stroke Di Wilayah Kerja Puskesmas Kuin Raya - Izma Daud; anas nasrullah; Zaqyyah Huzaifah (Jurnal Ilmiah JKA (Jurnal Kesehatan Aeromedika), 2025)
Stroke is one of the leading causes of death worldwide, ranking third after coronary heart disease and cancer. There are two main types of stroke: ischemic and hemorrhagic, which can affect various aspects of the lives of those affected. Timely and appropriate treatment during the golden window, which lasts about three hours after a stroke occurs, is crucial to reducing the risk of disability. In Indonesia, public awareness regarding stroke symptoms and initial management steps remains relatively low, contributing to the high incidence of stroke. This study aims to analyze the impact of BE-FAST educational videos on the knowledge of families of stroke patients at Puskesmas Kuin Raya. The research method employed is a pre-experimental design with a one-group pre-test and post-test approach. The results indicate that before the intervention, 56.38% of family members of stroke patients had a sufficient level of knowledge, while after the intervention, 61.70% showed an improvement to a good level of knowledge. The Wilcoxon test yielded a p-value of 0.001, indicating a significant effect of the BE-FAST educational video on enhancing the knowledge of families of stroke patients. This study recommends that Puskesmas provide more engaging and effective educational media to increase public awareness and knowledge about stroke.